Ergonomic intervention program for office workers: a case study about its effect in computer vision syndrome and musculoskeletal discomfort. - Cardoso, Bárbara; Mateus, Catarina; Magalhães, Rúben; Rodrigues, Matilde A. (Ergonomics, 2025)
This study aims to develop and implement an ergonomic intervention program at the workplace of knowledge workers, and to evaluate its impact on the reduction of Computer Vision Syndrome (CVS) and musculoskeletal symptoms. 84 workers were part of the study (mean age 43.2 ± 9.7 years). The intervention included training, delivery of a packaging of artificial tears, and adjustments in workstations. It was conducted intensively along 6 weeks. Data was collected on-site, with questionnaires administered pre-intervention, 2 months after, and 4 months after. Participants exhibited behavioural changes, especially in workplace adjustments and visual rest. By the intervention's end, over 90% had correctly adjusted screens and adopted appropriate postures, while 42.7% adhered to the 20x20x20 rule. CVS severity and prevalence decreased, but not significantly across the three time points. Significant improvements were observed in upper back and neck musculoskeletal symptoms at the end of workdays. Findings suggest that an ergonomic intervention program can benefit employees by reducing visual and musculoskeletal symptoms. PRACTITIONER SUMMARY: This study addresses CVS and MSDs, commonly experienced by individuals working with display screen equipment. It was emphasised the significance of ergonomic interventions in reducing musculoskeletal discomfort. The major finding was the positive behavioural changes, such as improved workplace adjustments and visual rest practices.